Odpowiedzi

2010-02-17T15:57:43+01:00
A) 5(n+1)-10=3n+1
5(3+1)-10=3*3+1
15+5-10=9+1
10=10 TAK

b) 2(a+1)-3(a-5)=7a
2(2+1)-3(2-5)=7*2
4+2-6+15=14
15=14 NIE

c)3x(x-5)=(x-2)(3x-3)
3*-1(-1-5)=(-1-2)(3*-1-3)
3+15=3+3+6+6
18=18 TAK
2 4 2
2010-02-17T16:00:27+01:00
A) 5(3+1)-10=3 x 3 +1
20-10=9+1
10=10
b)2(2+1)-3(2-5)=7x2
6-3x(-3)=14
6-9=14
-3=14
c)3(1-5)=(1-2)(3-3)
-12=-1
1 5 1
2010-02-17T16:02:41+01:00
A) 5 * (3+1) - 10 = 3*3+1
10 = 10
L = P

b) 2 * (2+1) - 3* (2-5) = 7*2
6-9 = 14
-3 = 14
L =/= P

c) 3*(-1) * (-1-5) = (-1-2) * [3*(-1)-3]
-15 = -7
L =/= P

Nie wiem czy dobrze.. ;P